Kritik Terhadap Oposisi Biner Pada Novel Animal Farm: Teori Dekonstruksi Jacques Derrida - Zullyansyah, Alfatan; Fauziah, Isma; Suci Novianti, Wulan; Alandira , Palendika; Zullyansyah , Alfatan; Alandira, Palendika (Institut Agama Islam Negeri Metro, 2025)
This research aims to analyze the binary oppositions found in the novel Animal Farm by George Orwell using Jacques Derrida’s theory of the deconstruction of binary oppositions. This qualitative research employs a descriptive analytical approach. The material object of this study is the novel Animal Farm, while the formal object is Jacques Derrida’s theory of the deconstruction of binary oppositions. The focus of the research is on the binary oppositions present in the text of Animal Farm, while the content analysis method is used to examine the text and identify the forms of binary oppositions in the novel’s characters. The results of the study show that Animal Farm contains many binary opposition texts that require interpretation. The final conclusion is that the novel presents binary opposition texts that must be dismantled using Jacques Derrida’s theory of deconstruction, resulting in new concepts such as animals conducting research.